Influence of long -term thermal cycling and masticatory loading simulation on bond strength of roots filled with epoxy resin and calcium silicate based sealers - Ahlam Smran; Mariam Abdullah; Norasmatul Akma Ahmad; Ali Alrahlah; Nassr AL-Maflehi; Abdulaziz Samran (BMC, 2023)
Abstract Background The aim of this study was to evaluate the effect of thermal and mechanical cyclic aging using a mastication simulator on push-out bond strength of mandibular premolars obturated with AH Plus and BioRoot RCS root canal sealers. Methods With REVO-S files up to SU/0.06 taper, 48 single-rooted premolar teeth were instrumented. The teeth were randomly divided into two main groups (n = 24) based on the two root canal sealers used (AH Plus and BioRoot RCS). All teeth were obturated with h matched-taper single-cone. Each main group was then subdivided into three subgroups (A, B, and C) (n = 8). Group A served as the negative control group (no-thermocycling aging). While groups B and C were subjected to thermal changes in a thermocycler machine (15,000 and 30,000 thermal cycles, respectively), followed by two different dynamic loading periods, 3 × 105 and 6 × 105 in a masticatory simulator with a nominal load of 5 kg at 1.2 Hz which represent roughly 1½ and 3 years of clinical function respectively. 2 mm slice at 3 levels, apical, middle, and coronal, to obtain 3 sections were prepared and subjected to push-out test using a universal testing machine. Statistical analysis was performed using analysis of variance (ANOVA) followed by a Tukey post hoc comparisons test and an independent T-test. A significance level of 5% was used. Results After thermal-mechanical cyclic aging, the two root canal sealers showed a significantly decreased in push-out bond strength (p < 0.05), however, AH Plus had significantly higher bond strength values than BioRoot RCS after cycling aging. Conclusions It could be concluded that thermal-mechanical cyclic aging had a significant impact on the outcome of the dislodgment resistance of AH Plus and BioRoot RCS.